2005
DOI: 10.1255/ejms.722
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Structural Characterisation of Carboxy-Terminal Polypeptides and Antibody Epitopes of Alzheimer's Amyloid Precursor Protein Using High-Resolution Mass Spectrometry

Abstract: Alzheimer's disease (AD) is the most common cause for human age-related dementia, characterised by formation of diffuse plaques in brain that are directly involved in AD pathogenesis. The major component of AD plaques is beta-amyloid, a 40 to 42 amino acid polypeptide derived from the amyloid precursor protein (APP) by proteolytic degradation involving the specific proteases, beta-and gamma-secretase acting at the N- and C- terminal cleavage site, respectively. In this study we have prepared polypeptides compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…In order to characterize the possible effect of the sequence environment of an NTresidue, the affinities and specificities of the monoclonal anti-3-NT antibody (legend to Figure 1) used for the proteolytic affinity extraction-MS analysis were assessed by an indirect ELISA method [33], using synthetic Tyrnitrated peptides comprising all tyrosine residues in ECP (Table S1, Figure S7; Supporting Information). The Tyr 33 -nitrated peptide ECP (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) showed substantially higher affinity compared with all other nitrated ECP peptides; in contrast, the Tyr 98 -nitrated peptide which is completely buried in the protein structure, revealed only minimal affinity. These results showed that the affinity differences between the nitrated ECP peptides correlate with a specific sequence environment of the tyrosine residues.…”
Section: Site Selectivity Of Tyrosine Nitration In Proteinsmentioning
confidence: 97%
See 3 more Smart Citations
“…In order to characterize the possible effect of the sequence environment of an NTresidue, the affinities and specificities of the monoclonal anti-3-NT antibody (legend to Figure 1) used for the proteolytic affinity extraction-MS analysis were assessed by an indirect ELISA method [33], using synthetic Tyrnitrated peptides comprising all tyrosine residues in ECP (Table S1, Figure S7; Supporting Information). The Tyr 33 -nitrated peptide ECP (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) showed substantially higher affinity compared with all other nitrated ECP peptides; in contrast, the Tyr 98 -nitrated peptide which is completely buried in the protein structure, revealed only minimal affinity. These results showed that the affinity differences between the nitrated ECP peptides correlate with a specific sequence environment of the tyrosine residues.…”
Section: Site Selectivity Of Tyrosine Nitration In Proteinsmentioning
confidence: 97%
“…In contrast, the direct identification of nitrations without affinity-extraction using HPLC-MS, such as in the auto-nitration site of eosinophilperoxidase (EPO) at Tyr 349 required highly purified protein and was only obtained after scrutinous HPLC separation of Figure 3. Identification of the tyrosine nitration site at Tyr −33 in eosinophil-derived neurotoxin by nano-ESI-FTICR-MS of the thermolysine peptide fragmnent, EDN (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). The modification denoted with X corresponds to carbamidomethylation at Cys-37.…”
Section: Proteolytic Affinity-mass Spectrometry Approach For Identifimentioning
confidence: 99%
See 2 more Smart Citations
“…These results and the most recent clinical studies confirming the epitope specificity (ADPD Congress, March 14-17, 2007, Salzburg, Austria) emphasize the therapeutic potential of plaque-specific antibodies. Using epitope excision -mass spectrometry and alanine scanning mutagenesis, we have previously shown that the mouse monoclonal 6E10 antibody, directed against β-amyloid (1-17), recognizes the same short epitope (FRHDSGY) at the N-terminus of Aβ, as did the antibodies resulting from active immunization of transgenic mice with Aβ(1-42) (11,12). Therefore, it is our hypothesis that primary structure details of this plaque-specific antibody (6E10) will provide a better understanding of the antigen recognition process at the molecular level and contribute to the development of more effective vaccines.…”
Section: Introductionmentioning
confidence: 99%